Characterization of Clostridioides difficile isolates recovered from hospitalized patients and the hospitals environment and air: A multicenter study. (October 2019) - Aliramezani, Amir; Talebi, Malihe; Golbabaei, Farideh; Baghani, Akram; Marjani, Majid; Afhami, Shirin; Hajabdolbaghi, Mahbobeh; Boroumand, Mohammad Ali; Kuijper, Ed J.; Douraghi, Masoumeh
Abstract: In healthcare settings, contamination of environment with toxigenic and hypervirulent Clostridioides difficile strains is a serious concern. Here, we assessed whether patients with C. difficile have a role to play in the dissemination of C. difficile in our settings or other sources are implicated in its circulation. A total of 700 fecal specimens and 1435 environmental samples from surfaces, equipment and air of rooms occupied by patients suspected of C. difficile infection were taken from 4 tertiary hospitals in Tehran, Iran between April 2016 and August 2017. Antibiotic susceptibility testing and detection of resistance genes were performed for the environmental isolates. The clinical and environmental isolates of C. difficile were subjected to Pulsed Field Gel Electrophoresis (PFGE) analysis. Forty three (6.14%) and 2 (0.13%) isolates of C. difficile were recovered from the clinical and environmental samples, respectively. In the clinical settings, 2 patients were suspected of recurrent C. difficile infection. Thirty distinct pulsotypes were found among the C. difficile isolates including 28 singletons and 2 common types. One of the two environmental isolates was isolated from floor in the Medical ward, of pulsotype/ribotype/toxinotype PT10/New ribotype/toxinotype V, harbored cdtA / B and tcdC-A, and resistant to ciprofloxacin. The other one was isolated from air of a room in ICU, assigned to PT11/RT001/toxinotype 0, belonged to tcdC-sc3 genotypes and resistant to metronidazole. The environmental isolates did not generate amplicons in PCR assays targeting vanA and nim genes. This study provided evidence for dissemination of genetically diverse strains of C. difficile in hospitalized patients, presence of C. difficile in hospital air, existence of binary toxin positive/antibiotic-resistant isolate on the floor and intra-hospital dissemination of this pathogen. Highlights: Dissemination of genetically diverse strains of C. difficile in hospitalized patients. Presence of C. difficile in hospital air. Existence of an antibiotic-resistant isolate of C. difficile on the floor. Intra-hospital dissemination of C. difficile.